Faktor Internal dan Eksternal Perbankan Syariah yang Mempengaruhi Tindakan Perataan Laba - Ros Melinda; Setiawan (Journal of Applied Islamic Economics and Finance, 2020)
The purpose of this study is to find out and analyze internal factors and external factors of Islamic banking which can affect the practice of income smoothing. This research was conducted at sharia commercial banks in Indonesia for the period 2013 to 2017. The population in this study amounted to 11 Islamic Commercial Banks. After sampling technique using a purposive sampling method, 10 Islamic banks were obtained which will be used as samples in the study. Whereas to see the influence of the independent variables on the dependent variable used panel data regression analysis method. Based on the results of the study it is known that simultaneously, profitability (earnings before tax and provisions), the amount of financing, Non-Performing Financing, Good Corporate Governance (the existence of the Sharia Supervisory Board), Gross Domestic Product, and the inflation rate affect income smoothing. While partially, only the variable profitability (earnings before tax and provisions), the amount of financing, and Non-Performing Financing that influence the practice of income smoothing in Islamic banking in Indonesia.